Aneurysm of extracranial internal carotid artery: A case report - (:unkn) unknown (My University, 2009)
A 42 year old man was referred to our hospital with a pulsatile left neck mass which had been diagnosed and treated as a reactive cervical lymphadenopathy for 3 months before referral. Diagnosis of an extracranial aneurysm of the left proximal internal carotid artery was made by magnetic resonance imaging angiography and digital subtraction angiography. Open surgical repair was performed by resection of the aneurysm and interposition of a reversed segment saphenous vein graft. Extracranial carotid artery aneurysms are uncommon pathologies and still challenging to diagnosis and treatment strategy. Awareness of this rare pathology in the differential diagnosis of head and neck masses would facilitate the diagnosis and prevent complications like cerebral thromboembolism. Surgical treatment is still regarded as a gold standard in the treatment of these cases. In this report, we presented a patient with an incidentally diagnosed aneurysm of extracranial internal carotid artery.
Keywords: Aneurysm; Extracranial internal carotid artery; Surgical treatment